Description of Extraordinary Events of Dengue Hemorrhagic Fever In Belu Regency, East Nusa Tenggara Province 2020 - Luan, Werenfridus Leonardo Nando (Institute of Topical Disease Universitas Airlangga, 2021)
Belu Regency is located in the province of East Nusa Tenggara (NTT), Indonesia and is an endemic area for dengue fever. Nationally, until June 2020, there were 16,320 cases of dengue fever with a CFR of 0.009%, while in Belu Regency there were 820 cases recorded until June 2020 with a CFR of 0.97%. This study aims to describe the outbreak of DHF by person, place and time as well as the distribution of cases in Belu Regency. this research is descriptive observational with case series design. The source of research data is secondary data on dengue cases obtained from the 2016-2019 Dengue Hemorrhagic Fever (DHF) Report and the DHF outbreak report in January-June 2020, the Belu District Health O ce. DHF cases in Belu Regency until June 2020 were 820 cases with symptoms of fever 2-7 days by 100% and supported by laboratory platelet examinations of 73%. The highest IR rate until June 2020 is 367 per 100. 000 residents with a CFR of 0.97% spread over 12 sub-districts of Belu Regency. The highest IRs (>20 per 10,000 population) are Atambua city, South Atambua, East Tasifeto, West Atambua, Kakuluk Mesak and West Tasifeto subdistricts. The majority of DHF in the age group 5-14 years 521 cases (27.1%) with female sex as many as 495 cases (51.51%). DHF cases were found since the first epidemiological week at the beginning of the year with peak cases at the 13th week. Belu Regency Is a dengue endemic area with an IR of 367/100,000 population with a CFR of 0.97%. The highest cases were in the 5-14 year age group and spread across 12 sub-districts of Belu Regency.